A deceptive enemy: unmasking toxoplasma encephalitis IRIS in HIV hepatitis B coinfection individual with tuberculosis - Cheong, Xiong Khee; Zainulabid, Ummu Afeera; Kori, Najma; Periyasamy, Petrick (Elsevier Ltd, 2025)
Immune Reconstitution Inflammatory Syndrome (IRIS) is a paradoxical inflammatory response that is associated with HIV-infected individuals following initiation of antiretroviral therapy (ART), particularly in those with low CD4 and high viral load. The diagnosis of central nervous system (CNS) IRIS is challenging due to its varied manifestations and similarity to other opportunistic infections. Although Toxoplasma gondii encephalitis is a common HIV-related CNS infection, unmasking CNS-IRIS associated with toxoplasma infection is rarely reported. We described a young male with advanced HIV, hepatitis B, and disseminated tuberculosis who developed Toxoplasma encephalitis IRIS after ART initiation.